Faktor Penghambat “Komunikasi Antarbudaya” (Kajian Islam dan Kearifan Lokal Perspektif Komunikasi Antarbudaya) - Wakidul Kohar (AL MUNIR : Jurnal Komunikasi dan Penyiaran Islam, 2010)
Some psychological factors that affect expectations when communicating with people from other cultures. These factors are the social cognitive and intergroup behavior, including culture shock, ethnocentrism, prejudice and stereotypes. According to experts, these factors can emerge and activation of which leads to problems of intercultural communication. Based on the ethnography of intercultural communication context, the picture of ethnic Minang as communicated by ethnic Javanese, or vice versa. In the context back to the village, into the tribe and the implementation of “Adat Basandi Syarak-Syarak Basandi Kitabullah”, as a variation of Islamic and local wisdom, suggesting that the cultural component is owned by every member of the culture affected the way we communicate.